Cheias: análise de frequências e regionalização de quantis - Pinheiro, Mário Cicarelli (1982)
The main purpose within this work is to selecting a mehod that best estimate future flood flow frequencies. By the way, many probability distributions, usually applied in flood frequency analysis, combined with differents parameters estimation methods have been considered. ln order to evaluate the goodness of fit of the functions to the data, the Chi-Square, Kolmogorov-Smirnov and some split-record testing have been used. A multiple-regression model and the Wakeby distribution have been also used to regionalize the quantiles for some return periods, to establish a flood frequency curve at sites where no streamflow observations have been taken and to improve the individual site estimates. The variables used were the annual maximum of daily peak, daily mean discharge, and the 3-day, 7-day, and 15-day volumes. The methodology was applied to some streamflow stations in the Southeastern and Southern regions of Brazil.